Formulation and Physical Stability Aromatherapy Medicated Oil of Red Ginger (Zingiber officinale var rubrum) - Pramana, I Kadek Bagus Ari; Dira, Made Asmarani; Damayanti, Ida Ayu Manik; Antari, Ni Wayan Sukma (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Aromatherapy products for health relax the body, refresh the mind, and act as a placebo in treating diseases. The more modern aromatherapy medicated oil innovation has high competitiveness in its distinctive aroma and packaging without reducing pharmacological effectiveness. One source of essential oil is red ginger (Zingiber officinale var rubrum), which has pharmacological effects such as antioxidant, anti-inflammatory, analgesic, and anti-carcinogenic. This research aims to prepare, formulate, perform a physical evaluation, and conduct hedonic testing of red ginger aromatherapy medicated oil. This research is experimental research with a posttest group design research design. The physical evaluation results, including organoleptic tests on color, showed that preparations F0 to F3 were precise, yellow +, yellow ++, and yellow +++, respectively. The aroma shows preparations F0 to F3, respectively, the smell of menthol to the typical aroma of red ginger (strong), and the texture F0 to F3 shows a liquid texture. The homogeneity test showed that preparations F0 to F3 were homogeneous. The pH test showed that the pH value of the preparation ranged between pH 5.5 and 6.2 for preparations F0 to F3. This study concluded that the red ginger aromatherapy medicated oil formulation with a concentration of 2%, 4%, and 6% has good physical quality.